THE INFLUENCE OF TEACHERS' TEACHING SKILLS THROUGH ACHIEVEMENT MOTIVATION ON THE LEARNING ACHIEVEMENT OF YPIS MAJU BINJAI STUDENTS - Muhammad Indra Gunawan; Mesra B (Penerbit Lafadz Jaya, 2023)
The purpose of this research was to analyze and investigate the role of achievement motivation in mediating the relationship between teaching skills of teachers and students' learning achievement at YPIS Maju Binjai. In the context of achievement motivation. The type of research in this study was quantitative associative. The research was conducted at YPIS Maju Binjai. The population in this study consisted of 80 teachers. The sampling technique used was saturated sampling, where the entire population was taken as the sample. The data collection technique used is through distributing questionnaires. The data analysis in this study was carried out using Smart PLS 3.0 with path analysis model. The results of this research indicate that: 1) teaching skills of teachers have a direct and significant influence on achievement motivation, which is evidenced by the T-statistic value of 239.555 > 1.96 and P-Value of 0.000 < 0.05. 2) Teaching Skills of Teachers have a significant effect on Students' Learning Achievement with a T-Statistic value obtained of 2.200 > 1.96 and P-Value of 0.031 < 0.05. 3) Achievement Motivation has a direct and significant influence on Students' Learning Achievement with a T-Statistic value of 4.642 > 1.96 and P-Value of 0.000 < 0.05. 4) Achievement motivation is able to mediate the teaching skills of teachers in influencing students' learning achievement at YPIS Maju Binjai with a T-Statistic value of 4.384 > 1.96 and P-Value of 0.000 < 0.05, which means that indirectly teaching skills of teachers influence students' learning achievement mediated by achievement motivation.